2017
DOI: 10.1364/ome.7.000712
|View full text |Cite
|
Sign up to set email alerts
|

Optical quality ZnSe films and low loss waveguides on Si substrates for mid-infrared applications

Abstract: Zinc Selenide (ZnSe) is a promising mid-infrared waveguide material with high refractive index and wide transparency. Optical quality ZnSe thin films were deposited on silicon substrates by RF sputtering and thermal evaporation, and characterized and compared for material and optical properties. Evaporated films were found to be denser and smoother than sputtered films. Rib waveguides were fabricated from these films and evaporated films exhibited losses as low as 0.6 dB/cm at wavelengths between 2.5 µm and 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…For the Zn 0.5 Cd 0.5 Se-6 and Zn 0.5 Cd 0.5 Se-10 alloy QDs (Figure 6d), the O–C=O binding energy peak of oleic acid also appears at 533.1 eV. We also observed that the binding energy peak at 529.9eV is attributed to O 2− in ZnO, thus confirming the formation of ZnO [45]. Consequently, the addition of high OLA contents could form ZnO/Zn 0.5 Cd 0.5 Se QDs in this chemical reaction process.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…For the Zn 0.5 Cd 0.5 Se-6 and Zn 0.5 Cd 0.5 Se-10 alloy QDs (Figure 6d), the O–C=O binding energy peak of oleic acid also appears at 533.1 eV. We also observed that the binding energy peak at 529.9eV is attributed to O 2− in ZnO, thus confirming the formation of ZnO [45]. Consequently, the addition of high OLA contents could form ZnO/Zn 0.5 Cd 0.5 Se QDs in this chemical reaction process.…”
Section: Resultssupporting
confidence: 56%
“…The Se 3d 5/2 and Se 3d 3/2 peaks (all samples) with binding energies of 53.7 and 54.6 eV, respectively, are attributed to the Se 2- in CdSe and ZnSe, thus confirming the formation of CdSe and ZnSe [42,43], as presented in Figure 6b. In Figure 6c, one peak with binding energy of 1021.2 eV can be observed for Zn 0.5 Cd 0.5 Se, Zn 0.5 Cd 0.5 Se-4, and Zn 0.5 Cd 0.5 Se-6 alloy QDs, which is attributed to Zn 2+ existing in the form of ZnSe [44,45]. For the Zn 0.5 Cd 0.5 Se-6 and Zn 0.5 Cd 0.5 Se-10 alloy QDs, the two peaks with binding energies of 1021.1 and 1022.7 eV (Figure 6c) can be found, which are assigned to Zn 2+ in the form of ZnO and ZnSe [44].…”
Section: Resultsmentioning
confidence: 99%
“…The recently demonstrated suspended Ge membrane devices hold the potential to fully utilize the broad transparency band of Ge, although optical functions of these devices at >3-μm wavelength are yet to be realized [29,30]. Infrared-transparent chalcogenides and halides, on the other hand, can be monolithically deposited on Si or dielectric substrates via thermal evaporation or sputtering, with waveguides defined by using two compositions of different indices as core and cladding layers ( Figure 3K-L) [16,[31][32][33][34][35][36][37][38]. Compared to Si or Ge, the drawback of this approach is that chalcogenides and halides are generally not considered compatible with CMOS foundry processes.…”
Section: Waveguides and Passive Devicesmentioning
confidence: 99%
“…Among these sensors, optical gas sensors, namely, fiber sensors [8], [9], surface plasmon resonance sensors [10], [11], and waveguide-integrated sensors [12], [13], have the advantages of high sensitivity, fast response, and electromagnetic immunity [14]. Taking advantage of stateof-the-art CMOS technology, silicon-based waveguideintegrated sensors are most promising to be integrated with optoelectronic and electronic devices for achieving monolithically chip-integrated sensing, signal processing, and communication [15]. Therefore, they have attracted great attention in the past decades.…”
Section: Introductionmentioning
confidence: 99%